Pelestarian Hutan dalam Budaya Pertanian Nugal oleh Masyarakat Adat Dayak Kuhin di Desa Sapundu Hantu, Kabupaten Seruyan, Kalimantan Tengah - Mirza, M Yusril (Universitas Gadjah Mada, 2025)
The Dayak Kuhin community, native to Central Kalimantan Province, had a traditional agricultural culture called nugal, which was carried out once a year. Nugal was considered an agricultural culture that involved opening fields in the forest, but it was often associated with causing forest fires. To clarify the realities of the practice, this research aimed to explore the nugal process and associated forest conservation efforts by taking a case study of the Sapundu Hantu Village, Seruyan Hulu District, Seruyan Regency, Central Kalimantan Province. This research employed an ethnographic method and a thick description approach, utilizing qualitative data collected through participatory observation, in-depth interviews, archival records, and literature reviews. The results revealed that the nugal agriculture embodied rich local knowledge about forest conservation efforts reflected in each process. The community practiced the nugal agriculture carefully with adherence to customary norms that regulated forest management. The findings of this study address the prevailing negative stigma associated with the nugal culture as practiced by the Dayak Kuhin community.